Relevansi Nilai Net Income, Comprehensive Income, dan OCI terhadap Return Saham dan Book Value - Rahma Aliya Marta; Retno Rantika; Nurhasnah; Nur Rahmad Alif; Yosep Eka Putra (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the relevance of Net Income (NI), Comprehensive Income (CI), and Other Comprehensive Income (OCI) to stock returns and book value in technology sector companies listed on the Indonesia Stock Exchange for the period 2023–2025. This study employs a quantitative approach using secondary data obtained from companies’ annual reports. A purposive sampling technique was used, resulting in 45 observations. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that, when analyzed individually, NI, CI, and OCI do not have a significant relationship with stock returns. Conversely, these three variables were found to have a significant relationship with book value. Simultaneously, NI, CI, and OCI have a significant effect on both stock returns and book value. These findings indicate that investors in the technology sector tend to consider factors other than profit information when making investment decisions. However, profit and comprehensive income information still play a role in reflecting a company’s economic value, as reflected through book value